Marriott's strategic sustainability priorities in the Chinese hotel industry. (28th February 2020) - Wickham, Mark; French, Linda; Wong, Tommy
Using Mihalic et al.'s (2012) hotel sustainability business framework as its lens, this study provides an empirical analysis of a leading western hotel chain's sustainability priorities in its entry and subsequent operations in China's emerging hotel industry. A qualitative study of company documentation and semi-structured interviews with 12 senior managers at Marriott International in China indicated that seven sustainability strategies were prioritised by the chain (i.e., domestic employee development and satisfaction, resource allocation and education, guest satisfaction, domestic government engagement, the power to change participation, and the need to establish a positively differentiated labour-market position). This study and proposes a range of sustainability research opportunities in emerging hotel industry contexts. In addition to this, a range of practical implications for sustainability management in emerging hotel industry settings are presented.